Marketing Strategy For MSMEs In The Digital Era - Novieyanti Novieyanti; Mulya Rafika; Bhakti Helvi Rambe (PT Mattawang Mediatama Solution, 2023)
The purpose of this research is to find out how to increase income through social media such as social media, influencers and live streaming to increase sales to MSMEs. This study uses a quantitative approach that tests numbers and analyzes statistical tests, collects data, uses a sample of 100 respondents to get valid answers. The results of this study indicate that digital marketing or social media has a significant effect on increasing income at MSMEs, influencers have a significant effect on increasing income on MSMEs, and the last variable, namely live streaming, has a positive and significant effect on increasing income at MSMEs. The development of technology is currently very rapid and very influential for people in the business world. MSMEs must be able to compete and carry out business strategies in order to win the competition. By taking advantage of advances in digital technology, MSME actors can spread their product promotions on online shopping sites such as social media and so on, by creating useful and interesting video content and also using models as promotional tools for their products in an effort to attract customers to buy a product.